DIONNE BRAND, The Blue Clerk – Ars Poetica in 59 Versos - Howes, Hadley (Archivaria, 2020)
The Blue Clerk: Ars Poetica in 59 Versos. Dionne Brand. Toronto: McClelland & Stewart, 2019. 248 pp. ISBN 978-0-7710-0154-3